2015
DOI: 10.1186/s12967-015-0592-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-106b induces cell radioresistance via the PTEN/PI3K/AKT pathways and p21 in colorectal cancer

Abstract: BackgroundRadioresistance is a challenge in the treatment of patients with colorectal cancer (CRC). Individuals display different therapeutic responses to preoperative radiotherapy, and the need of targeted therapies is urgent. MicroRNAs (miRNAs) are involved in essential biological activities, including chemoresistance and radioresistance. Several research studies have indicated that miRNA played an important role in sensitizing cells to ionizing radiation (IR). MiR-106b, a member of the miR-106b-25 cluster, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 38 publications
6
104
1
Order By: Relevance
“…36 Moreover, miR-106b induced cell radioresistance, and miR-520g conferred drug resistance in colorectal cancer both by regulating p21 expression. 39,40 And, miR-224 promoted the chemoresistance of A549 cells to cisplatin by targeting p21 as well. 41 Our data that miR-33b-3p attenuated the cisplatin sensitivity of A549 cells by direct diminishing the p21 expression, was in consistent with above published literatures.…”
Section: Discussionmentioning
confidence: 99%
“…36 Moreover, miR-106b induced cell radioresistance, and miR-520g conferred drug resistance in colorectal cancer both by regulating p21 expression. 39,40 And, miR-224 promoted the chemoresistance of A549 cells to cisplatin by targeting p21 as well. 41 Our data that miR-33b-3p attenuated the cisplatin sensitivity of A549 cells by direct diminishing the p21 expression, was in consistent with above published literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes have been verified to be the targets of miR-106b, including transforming growth factor-β type II receptor, cyclin dependent kinase inhibitor 1A, DLC-1 Rho GTPase activating protein, signal transducer and activator of transcription 3 and mitogen-activated protein kinase 14 (7,(10)(11)(12). Phosphatase and tensin homolog (PTEN), a key negative regulator of the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway, is also a direct target of miR-106b (13). One previous study had reported that PTEN served as a tumor-suppressing gene in cancer invasion and metastasis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of PTEN by COX-2 inhibitors could induce cancer cell radiosensitivity (34). miRNA29a, miRNA21, miRNA16b could regulate radiosensitivity through targeting PTEN (35)(36)(37). PTEN/PI3K/AKT pathways were demonstrated mediating radiosensitivity (35).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA29a, miRNA21, miRNA16b could regulate radiosensitivity through targeting PTEN (35)(36)(37). PTEN/PI3K/AKT pathways were demonstrated mediating radiosensitivity (35). PTEN/Akt/HIF-1α feedback loop modulates miRNA210-induced radiosensitivity (37).…”
Section: Introductionmentioning
confidence: 99%